Comparison of Cross Sectional Areas of Median Nerve in Type 2 Diabetic Patients with Peripheral Neuropathy with Healthy Adult Subjects Measured by 2 D-B Mode High Resolution Ultrasonography (BIRDEM Medical Journal, 2017)
Background: Patients with diabetic peripheral neuropathy (DPN) have distal, symmetrical form of the disorder characterized by numbness, burning feet, pins-and-needles sensations and lightning pain. This study was designed to find out the difference between 2 Dimentional (D)-Brightness (B) mode high resolution ultrasonographically measured cross sectional areas of median nerve in type 2 diabetic patients with peripheral neuropathy and those of non-diabetic healthy adult subjects.Methods: This case-control study was done on 180 subjects aged 27-67 years in the department of Radiology and Imaging, BIRDEM from January 2012 to December 2013. Out of them 90 diabetic patients with peripheral neuropathy diagnosed electrophysiologically by nerve conduction study (NCS) were considered study group and age, sex and weight compatible 90 healthy subjects were considered as control group. Measurement of cross sectional areas of median nerve was performed first by the investigator himself purposefully, consecutively and subsequently confirmed by a radiologist in the department of Radiology and Imaging, BIRDEM, who did not know the subjects’ condition to eliminate bias. The major axis, minor axis and the cross sectional areas (CSA) of the median nerve were measured at the carpal tunnel.Results: In this study, the mean cross sectional areas (mm2) of median nerve healthy subjects was 7.78±1.00 mm2 and in diabetic patients with peripheral neuropathy was 13.67±2.97 mm2. The difference mean CSA of median nerve of diabetic subjects with peripheral neuropathy and control subjects were statistically significant (p